Kontranasari pada Tradisi Ziarah Kubur dalam Buku “Tak Ada Azab Kubur” Karya Agus Mustofa: Indonesia - Husaini, Ahmad Sa'dan; Fattah Abdillah , Achmad Rowie; Annisa, Devina Nur (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
The tradition of grave pilgrimage (ziarah makam) has long been rooted in Javanese culture, both before and after the arrival of Islam. This activity is generally understood as an expression of respect for ancestors as well as a means of praying for the souls of the deceased. Among Javanese Muslims, grave pilgrimage also serves as a spiritual and social expression that reflects the relationship between the living and the departed. However, a different perspective emerges from Agus Mustofa through his work “Tak Ada Azab Kubur”, which presents a counter-narrative to traditional beliefs about the afterlife and the concept of punishment in the grave. This study aims to analyze the critical reasoning proposed by Agus Mustofa concerning his interpretation of the concept of grave punishment and its implications for the tradition of grave pilgrimage in Java. The research employs a qualitative method with a descriptive-analytical approach, examining Agus Mustofa’s texts and thoughts systematically and situating them within the context of Javanese Islamic tradition. The findings reveal that Agus Mustofa offers a rational and contextual reinterpretation of the doctrine of grave punishment, challenging the literal understanding held by many believers. This study enriches the discourse of Islam in Java by opening a space for dialogue between tradition, spiritual interpretation, and modern rationality.